The double-stranded RNA-binding protein, Staufen1, is an IRES-transacting factor regulating HIV-1 cap-independent translation initiation. Issue 1 (6th December 2021) - Ramos, Hade; Monette, Anne; Niu, Meijuan; Barrera, Aldo; López-Ulloa, Brenda; Fuentes, Yazmín; Guizar, Paola; Pino, Karla; DesGroseillers, Luc; Mouland, Andrew J; López-Lastra, Marcelo
Abstract: Translation initiation of the viral genomic mRNA (vRNA) of human immunodeficiency virus-type 1 (HIV-1) can be mediated by a cap- or an internal ribosome entry site (IRES)-dependent mechanism. A previous report shows that Staufen1, a cellular double-stranded (ds) RNA-binding protein (RBP), binds to the 5'untranslated region (5′UTR) of the HIV-1 vRNA and promotes its cap-dependent translation. In this study, we now evaluate the role of Staufen1 as an HIV-1 IRES-transacting factor (ITAF). We first confirm that Staufen1 associates with both the HIV-1 vRNA and the Gag protein during HIV-1 replication. We found that in HIV-1-expressing cells, siRNA-mediated depletion of Staufen1 reduces HIV-1 vRNA translation. Using dual-luciferase bicistronic mRNAs, we show that the siRNA-mediated depletion and cDNA-mediated overexpression of Staufen1 acutely regulates HIV-1 IRES activity. Furthermore, we show that Staufen1-vRNA interaction is required for the enhancement of HIV-1 IRES activity. Interestingly, we find that only Staufen1 harboring an intact dsRNA-binding domain 3 (dsRBD3) rescues HIV-1 IRES activity in Staufen1 CRISPR-Cas9 gene edited cells. Finally, we show that the expression of Staufen1-dsRBD3 alone enhances HIV-1 IRES activity. This study provides evidence of a novel role for Staufen1 as an ITAF promoting HIV-1 vRNA IRES activity.